Über die Philosophie von Barbara Skarga – eine Anregung zur Auseinandersetzung mit ihrem Leben und Werk - Bogaczyk-Vormayr, Małgorzata (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2018)
Barbara Skarga (1919–2009) was one of the most important Polish Philosophers of 20th century. She was an expert in classical and contemporary French (e.g. Comte, Bergson, Lévinas) and German Philosophy (e.g. Kant, Hegel, Heidegger). In this paper I present some important biographical facts (participation in organized resistance in Vilnius, interments in Gulags) as well Skarga’s philosophical, mostly sociopolitical and ethical, ideas. I called its philosophical concept “philosophy of difference”.
On Philosophy of Barbara Skarga: An Approach to Get to Know Her Life and Work
Keywords: Barbara Skarga; Polish contemporary philosophy; philosophy of dialogue; metaphysics; difference; identity